ASSESSMENT OF FARMERS’ PERCEPTION ABOUT BEETAL GOATS IN PAKISTAN BY USING LOGISTIC REGRESSION - A. Waheed; M. S. Khan; M. M. Tariq (Journal of Animal and Plant Sciences, 2016)
Choice experiments with 64 choice sets of six attributes (each at two levels) of Beetal goats were performed. Randomly chosen choice sets were used in eight blocks, each with 8 choice sets. Eight choice sets of female and 8 for males were presented to each farmer and 32 farmers were surveyed. The data thus obtained in the form of “selected” or “not selected’ were put to analysis using Logistic regression in binary form. Farmers showed greater inclination towards economically important traits and showed lesser concern to beauty traits & body size. It is therefore suggested that for maximizing economic benefits, the goats should be kept and bred keeping in view the farmers’ preferences.
Keywords: Choice experiments; Beetal goats; logistic regression; farmer preference